Personalized Training Schedules for Retention and Sustainment of Cardiopulmonary Resuscitation Skills. Issue 1 (February 2022) - Oermann, Marilyn H.; Krusmark, Michael A.; Kardong-Edgren, Suzan; Jastrzembski, Tiffany S.; Gluck, Kevin A.
Abstract : Introduction: The study examined how the spacing of training during initial acquisition of cardiopulmonary resuscitation (CPR) skill affects longer-term retention and sustainment of these skills. Methods: This was a multiphased, longitudinal study. Nursing students were randomly assigned to 2 initial acquisition conditions in which they completed 4 consecutive CPR training sessions spaced by shorter (1 or 7 days) or longer (30 or 90 days) training intervals. Students were additionally randomized to refresh skills for 1 year every 3 months, 6 months, or at a personalized interval prescribed by the Predictive Performance Optimizer (PPO), a cognitive tool that predicts learning and decay over time. Results: At the end of the acquisition period, performance was better if training intervals were shorter. At 3 or 6 months after acquisition, performance was better if initial training intervals were longer. At 1 year after acquisition, compression and ventilation scores did not differ by initial training interval nor by 3-month or PPO-prescribed sustainment interval refreshers. However, 6-month interval refreshers were worse than the PPO for compressions and worse than 3 months for ventilations. At the final test session, participants in the personalized PPO condition had less variability in compression scores than either the 3- or 6-month groups. Conclusions: Results suggest that CPR learning trajectories may be accelerated by first spacing training sessions by days and then expanding to longer intervals. Personalized scheduling may improve performance, minimize performance variability, and reduce overall training time.